Mapping the scientific research on the gamma irradiated polymers degradation (1975–2018). (March 2020) - Girard-Perier, Nina; Dorey, Samuel; Marque, Sylvain R.A.; Dupuy, Nathalie
Abstract: The global research trend on the degradation of gamma irradiated polymers from 1975 to 2018 was studied with a bibliometric approach. With 1339 papers published during this period, the investigation showed a growing interest overtime since 1975. The main countries working on that topic are USA, China, Japan and Europe. From 1975 to 1998, Japan was the first country to publish in this field. From 1998 to 2008, USA came on the top whereas from 2009 to 2018 China detained the most papers published. Networks analysis based on countries, authors and keywords showed interesting facts. First, a worldwide collaboration is growing overtime. Secondly, a multi-technique approach is necessary to study the degradation of the gamma irradiated polymers. Different work areas were highlighted. First, the journal sources study reveals three main domains: the nuclear, the biomedical and the polymer science domain. In a second time, the biology domain is the most discussed domain regarding at the top five most cited publications. Finally, the biopharmaceutical domain is the most represented domain regarding at the tip five most recent publications. Highlights: Overview of the gamma irradiated polymers degradation field from 1975 to 2018 using bibliometric approach. Multi technique approach is used to study polymers degradation. Gamma irradiated polymers degradation field mainly distributed through biomedical, nuclear and polymer science.